Application of biochar derived from expansive shrubs and limestone improved acidic soil characteristics - Mebrahtu Haile; Emiru Birhane; Girmay Gebresamuel; Muyiwa S. Adaramola; Meley Mekonen Rannestad (Carbon Management)
Biochars were produced at 350 °C and applied at varying rates (0, 52, 104, and 156 Mg ha−1 and incubation times up to 120 days. Both biochars and limestone significantly improved soil properties like pH, electrical conductivity, cation exchange capacity (CEC), and nutrient availability. Limestone proved most effective, raising pH by 1.3 units on average and increasing EC and CEC, followed by Cadia purpurea- and Tarchonanthus camphoratus-based biochars. Biochars also increased pH, with Cadia purpurea showing the greatest effect (up to a 1.49 unit increase at the highest rate of application). These findings suggest biochar from these expansive plants holds promise for improving acidic soils. However, the optimal application rate, incubation times, and type of amendment (biochar or limestone) likely depend on specific soil characteristics and goals. Further research is needed to explore long-term effects, combined amendment approaches, and cost-effectiveness for long-term soil health, agricultural productivity, and environmental well-being.